1975
DOI: 10.1007/bf01007019
|View full text |Cite
|
Sign up to set email alerts
|

Cytochemical response of kidney, liver and nervous system to fluoride ions in drinking water

Abstract: Morphological and cytochemical studies on the squirrel monkey have been made after maintaining the sujects on pure distilled water and fluoridated distilled water for 18 months with the objective of determining the effect of fluoride on the activity of some hydrolytic and oxidative enzymes in the kidney, liver and nervous system. Daily water intake by individual animals was measured over the final 10 months of the animal's exposure to 0,1 and 5 ppm fluoride. Water consumption was considerably higher in the ani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

1980
1980
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 18 publications
1
15
0
1
Order By: Relevance
“…Other experiments carried out in Japan (Tohyama 1996), USA (Takahashi et al 2001) and Taiwan (Yang et al 2000) proved that various types of cancers are associated with fluoride. Further, studies also show that in animals, kidney damage occurs even at lower levels of fluoride exposure over a long time (Manocha et al 1975).…”
Section: Medical Perspectivementioning
confidence: 95%
“…Other experiments carried out in Japan (Tohyama 1996), USA (Takahashi et al 2001) and Taiwan (Yang et al 2000) proved that various types of cancers are associated with fluoride. Further, studies also show that in animals, kidney damage occurs even at lower levels of fluoride exposure over a long time (Manocha et al 1975).…”
Section: Medical Perspectivementioning
confidence: 95%
“…Many studies have been carried out on animals, and it has been found that kidney damage occur even at lower levels of fluoride exposure over long periods (Manocha 1975;Varner 1998). Fluoride levels in drinking water of only 0.4 mg/l have been shown to cause renal impairment (Junco 1972).…”
Section: Introductionmentioning
confidence: 99%
“…Effects in the kidneys are of the first to be seen in fluoride exposure of mammals (Taylor et al 1961;Taves et al 1970;Franscino 1972;Manocha et al 1975). The reason for this is considered to be the relative high concentrations of fluoride found in the kidneys and in the urine during exposure (Whitford & Taves 1973;Dahlgreen 1978).…”
mentioning
confidence: 99%